1999
DOI: 10.1002/(sici)1096-9071(199908)58:4<378::aid-jmv10>3.0.co;2-p
|View full text |Cite
|
Sign up to set email alerts
|

Human papillomavirus genotype spectrum in Czech women: Correlation of HPV DNA presence with antibodies against HPV-16, 18, and 33 virus-like particles

Abstract: Because the biological spectrum of human papillomavirus (HPV) genotypes present in cervical cancer lesions varies according to the geographical region studied, and because little genotype information is available for Central and Eastern European countries, we studied the endemic HPV-genotype spectrum in cervical samples collected from women visiting gynaecological departments of selected hospitals in the Czech Republic. In a series of 389 samples, 171 (44.0%) were positive for HPV DNA using a consensus-primer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
17
1

Year Published

2000
2000
2013
2013

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 36 publications
2
17
1
Order By: Relevance
“…Human studies have suggested that VLP assays have moderate-to-good type specificity. These studies demonstrate stronger associations of seroreactivity with detection of viral DNA in the cervix of the same type and with type-specific seroconversion after incident infection [20,[29][30][31][32]. Numerous studies indicate that VLP assays performed on serum samples have a sensitivity of ∼50% for cervical HPV infection that is detectable by polymerase chain reaction (PCR) [16,24,29,[33][34][35][36][37].…”
mentioning
confidence: 99%
“…Human studies have suggested that VLP assays have moderate-to-good type specificity. These studies demonstrate stronger associations of seroreactivity with detection of viral DNA in the cervix of the same type and with type-specific seroconversion after incident infection [20,[29][30][31][32]. Numerous studies indicate that VLP assays performed on serum samples have a sensitivity of ∼50% for cervical HPV infection that is detectable by polymerase chain reaction (PCR) [16,24,29,[33][34][35][36][37].…”
mentioning
confidence: 99%
“…HPV specific antibodies are more frequent in the sera of women with CIN or INCA than in healthy controls 10 and HPV DNA positive women show a significantly higher prevalence of HPV specific antibodies than HPV DNA negative women. [11][12][13] It has also been shown that women with anti-HPV 16 VLP antibodies are in higher risk of developing CIN or INCA than women without them. [14][15][16][17] Moreover, a relation has been found between the presence of antibody and the severity and prognosis of the disease.…”
mentioning
confidence: 99%
“…16,[19][20][21] In addition, rates of higher than 30% have been reported in many prevalence studies such as the study by Tachezy et al involving Czech women, with an HPV positivity rate of (44%) among 389 women. [22][23][24][25] Another study that investigated HPV DNA by PCR reported a rate of 43.8% among female sex workers in Bulgaria, whereas it was 38.9% in China and 66.8% in Peru. [26][27][28] Previous studies from Turkey suggested an HPV DNA positivity rate between 8.7% and 21.6 %.…”
mentioning
confidence: 99%